Study on the nonexistence of liquid miscibility gap in the Ce-Mn system - Tang C.; Du Y.; Xu H.; Hao S.; Zhang L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
To ascertain whether the liquid miscibility gap exists in the Ce-Mn system, 3 key alloys are prepared by arc melting the pure elements, annealed at specified temperature for 20 minutes, quenched in ice water and then subjected to X-ray diffraction (XRD) analysis for phase identification and to scanning electron microscopy (SEM) with energy dispersive X-ray analysis for microstructure observation and composition analysis. The XRD examination indicated that terminal solutions based on Ce and Mn exist in the water-quenched alloys. No compound was detected. Microstructure observation and composition analysis indicate the nonexistence of the liquid miscibility gap. The newly assessed Ce-Mn phase diagram was presented. .